Human Thriving and the Law - Foster, Charles (SpringerBriefs in Law,, 2018)
The idea of the Good Life - of what constitutes human thriving, is, implicitly, the foundation and justification of the law. The law exists to hold societies together; to hold in tension the rights of individuals as against individuals, the rights of individuals as against various types of non-humans such as corporations (and vice versa), and the rights of individuals individuals as against the state (and vice versa). In democratic states, laws inhibit some freedoms in the name of greater, or more desirable freedoms. The only justification for law is surely that it tends to promote human thriving. But what is the Good Life? What does it mean to live a thriving life? There has been no want of discussion, at least since the great Athenians. But surprisingly, since human thriving is its sole raison d'etre, the law has been slow to contribute to the conversation. This book aims to start and facilitate this conversation. It aims to: -make lawyers ask: 'What is the law for?', and conclude that it is to maximise human thriving -make lawyers ask: 'But what does human thriving mean?' -make judges and advocates ask: 'How can a judgment about the best interests of a patient be satisfactory unless its basis is made clear?'.